The growth of minds and cultures : a unified theory of the structure of human experience - Vanderburg, Willem H. (Vanderburg, Willem H. Technique and culture, 1985)
"In the second edition of this publication the author examines the growth of children's minds and their relationship to culture, their structures of experience act as as a kind of 'mental map' which is individually unique and culturally typical. A society can thus be understood as an ensemble based on a culture which creates the foundation for a coherent way of life, permitting large numbers of people to live together. Vanderburg shows how the culture of a society underlies its science, technology, economy, social structure, political institutions, morality, religion and art. As such it seeks to build bridges not only between the 'two cultures' but between all the sciences in order to gain a deeper understanding of our age."--